Factors That Determine Customer Loyalty Towards Bear Brand Milk Drink in The City of Banda Aceh - Rizal, Syamsul; Ismail (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Consumer attitudes are very determining in making decisions to buy a product. A person's attitude towards product attributes can vary due to beliefs and evaluations of the attributes of the product. Apart from that, there are other factors that also influence what will ultimately determine their interest in buying a product. To find out and analyze differences in consumer attitudes towards product attributes. To obtain information and data in this research the author conducted field research, namely research on buyers of health milk drinks in the form of pure Bear Brand milk. The research object is regarding customer or consumer loyalty towards Bear Brand milk drinks in Banda Aceh City. The research results show that Bear Brand milk is good for health if consumed regularly. Consumers buy Bear Brand milk; this is indicated by the Sig value. t in all attributes of consumer attitudes towards Bear Brand milk products studied is worth > from α = 0.05 (The test results obtained show that having knowledge for health in consuming Bear Brand milk with the main consideration being more visible is for health. Or in other words it is used as a pure milk drink shows an overall positive effect on maintaining health.